2019
DOI: 10.1128/jvi.01010-19
|View full text |Cite
|
Sign up to set email alerts
|

The Leader Protein of Theiler's Virus Prevents the Activation of PKR

Abstract: Leader (L) proteins encoded by cardioviruses are multifunctional proteins that contribute to innate immunity evasion. L proteins of Theiler’s murine encephalomyelitis virus (TMEV), Saffold virus (SAFV), and encephalomyocarditis virus (EMCV) were reported to inhibit stress granule assembly in infected cells. Here, we show that TMEV L can act at two levels in the stress granule formation pathway: on the one hand, it can inhibit sodium arsenite-induced stress granule assembly without preventing eIF2α phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…TMEV L pro disrupts PKR function by preventing the interaction between PKR and viral dsRNA during virus infection, thus, inhibiting the consequent PKR-mediated eIF2α phosphorylation and antiviral response. Interestingly, this study found that TMEV L pro did not directly interact with either dsRNA or PKR, and the exact mechanism remains unknown [88].…”
Section: Evasion or Targeting Of Isgsmentioning
confidence: 70%
“…TMEV L pro disrupts PKR function by preventing the interaction between PKR and viral dsRNA during virus infection, thus, inhibiting the consequent PKR-mediated eIF2α phosphorylation and antiviral response. Interestingly, this study found that TMEV L pro did not directly interact with either dsRNA or PKR, and the exact mechanism remains unknown [88].…”
Section: Evasion or Targeting Of Isgsmentioning
confidence: 70%
“…Some viruses evolved various strategies to block SG formation during infection, which counteracted its antiviral effects ( 13 , 20 , 36 , 37 ). And some viruses exploited SG components to facilitate their replication ( 16 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Picornavirus 3C or L protein inhibited SG assembly via targeting G3BP1 for cleavage ( 29 , 40 , 41 ). TMEV L protein prevented the activation of PKR via dampening the responsiveness of PKR to dsRNA, thus inhibiting SG formation ( 36 ). To our surprise, no cleavage band was detected when 293T cells were co-transfected with 3C and G3BP1 ( Figure 7B ).…”
Section: Discussionmentioning
confidence: 99%
“…Host 463 suppression by multifunctional viral proteins is a critical determinant of success for all RNA 464 viruses [51], including Human Immunodeficiency Virus (HIV) [81]. Viral RNAs can suppress 465 host RNA interference pathways involved in antiviral immunity [82] or block the abilities of host 466 antiviral proteins to engage with viral dsRNAs and mount an immune response [83]. 467…”
Section: Evolutionary Patterns 428mentioning
confidence: 99%